Postoperative Delirium After Vascular Surgery - Simões, V (2015)
OBJECTIVES: The objectives of this study were to determine the incidence of Postoperative Delirium and to identify specific perioperative risk factors in patients undergoing Vascular Surgery. Other goals were to study its impact in hospital length of stay and to create an algorithm to deal with patients under suspicion of Postoperative Delirium. MATERIAL AND METHODS: A total of 56 consecutive vascular surgery patients were prospectively evaluated. Exclusion criteria were age less than 18, dementia, abnormal level of consciousness, psychiatric disorder and visual or hearing impairment. Mini Mental State Examination were applied during pre-anesthetic visit. In patients with clinical indicators of delirium the Confusion Assessment Method was applied. Patients were assessed during 5 days after surgery. RESULTS: The overall incidence of delirium was 12,5%, developped mostly by the second to fifth postoperative day. Patients with delirium presented moderate to severe pain. Patients who received combined general and regional anesthesia didn't develop delirium. The median hospital length of stay was 21 in patients with delirium and 7 days in patients without (p 0.001). CONCLUSIONS: The overall incidence of postoperative delirium was lower than previously reported. The incidence of delirium was higher in ICU patients and pain was associated with postoperative delirium suggesting the opportunity to control postoperative factores. The development of delirium in the second and fifth day indicated the need for early and more prolonged preventive and diagnosing measures. Clinical and costly considerations of prolonged hospital stay shown in this cohort warrant strong debate strategies to be applied.